2013
DOI: 10.1002/aur.1308
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Mind in Children with Autism Spectrum Disorder: Do Siblings Matter?

Abstract: Research indicates a positive relation between the sibling constellation and theory of mind (ToM) development in typically developing (TD) children. Less is known about this association in children with autism spectrum disorder (ASD). The current study examined the association among the presence and number of siblings, birth order, and false belief (FB) understanding in children with ASD and a TD comparison group. Two FB tasks (change of contents and change of location) and the Peabody Picture Vocabulary Test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
18
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 43 publications
7
18
0
1
Order By: Relevance
“…152 Autistic children that have an older sibling (i.e., that have consistent access to social partners) score higher in ToM tests than those without older siblings. 153 These findings are consistent with a recent study that demonstrated the impact of social environment on brain anatomy; monkeys experimentally introduced to larger social groups showed an increase in grey matter volume in two brain areas implicated in social cognition, the mid-superior temporal sulcus and the rostral prefrontal cortex. 154 Together, these studies demonstrate that socio-cognitive skills are present in early life but can be tuned by social interactions.…”
Section: The Ontogeny Of Friendshipsupporting
confidence: 92%
“…152 Autistic children that have an older sibling (i.e., that have consistent access to social partners) score higher in ToM tests than those without older siblings. 153 These findings are consistent with a recent study that demonstrated the impact of social environment on brain anatomy; monkeys experimentally introduced to larger social groups showed an increase in grey matter volume in two brain areas implicated in social cognition, the mid-superior temporal sulcus and the rostral prefrontal cortex. 154 Together, these studies demonstrate that socio-cognitive skills are present in early life but can be tuned by social interactions.…”
Section: The Ontogeny Of Friendshipsupporting
confidence: 92%
“…First, in the absence of a family history, the average age of diagnosis for both ASD and FXS is at 3 years of age despite symptoms present in the first year of life (Bailey, Raspa, Bishop, & Holiday, 2009; Matthews, Goldberg, & Lukowski, 2013). Thus, refined characterization of the infant phenotype in ASD and FXS has the potential to identify markers that could be useful for earlier and more specific diagnosis resulting in early treatment.…”
mentioning
confidence: 99%
“…The researchers suggest friendships offer one-on-one social experiences with familiar peers, over extended periods of time, which provide children with ASD more opportunities to develop and practice their social skills such as sharing and cooperation [52]. Although there is a substantial amount of research on the links between perspective-taking, prosocial behavior, and peer relationships in typically developing children, more research is needed examining these relationships in children with ASD to better understand how to foster friendship development in these populations [49,53].…”
Section: The Important Role Social Perspectivetaking Plays In Childrementioning
confidence: 99%
“…Research by Farhadian and colleagues revealed that birth order predicted false-belief understanding in typically developing children [98]. Indeed, a significant amount of research suggests that most of the benefits come from older as opposed to younger siblings [53,99,100]. Language is a medium through which children come to learn about the unobservable mental states of other individuals [76].…”
Section: The Role Of Siblings In the Development Of Social Perspectivmentioning
confidence: 99%
See 1 more Smart Citation